Influence of Exotic Bird and Wildlife Trade on Avian Influenza Transmission Dynamics: Animal-Human Interface - Burgos, Sigfrido; Burgos, Sergio A. (International Journal of Poultry Science, 2007)
Legal and illegal global trade of exotic bird and wildlife facilitates dynamic disease transmission mechanisms that threaten livelihoods, international trade, livestock production and native wildlife populations. Disease outbreaks resulting from exotic bird and wildlife trade have caused substantial economic damage globally. Contacts between wildlife, poultry and humans facilitate inter-species disease transferences.